Flip Bottle Learning Media to Improve Learning Outcomes of Class X Students of MA Muhammadiyah Pekanbaru - Nurbela, Intan; Supentri, Supentri; Yusmak, Rini (Riviera Publishing, 2025)
This study aims to improve students' learning outcomes through the implementation of flip bottle learning media among tenth-grade students at MA Muhammadiyah Pekanbaru. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. Data were collected through learning outcome tests, student activity observation sheets, and documentation. The results indicate a significant increase in student engagement and participation during the learning process after the implementation of the flip bottle media. Moreover, there was an improvement in students' mastery of learning outcomes from Cycle I to Cycle II, demonstrating that the game-based learning media effectively enhanced conceptual understanding and learning motivation. Therefore, the flip bottle media is proven to be an effective and innovative alternative to improving classroom learning quality.